Copper-Based Coordination Polymer Nanostructure for Visible Light Photocatalysis - Jiang, Hai-Ying (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.